ANALISIS PERSEDIAAN BAHAN BAKU MARTABAK NIKITOP DI KABUPATEN PURWOREJO - , (Politeknik Sawunggalih Aji, 2021)
Martabak Raw Material Supplies NIKITOP is a business that operates in the field of selling martabak which serves the general public. The inventory system is still carried out manually, that is, every time stock comes in and stock goes out, it is recorded in a book, which often makes the process of searching for data difficult, and also requires more space and time. This research method uses quantitative and qualitative methods to find out information about raw material inventory management. One way to make it easier to develop a merchandise inventory management information system is to use the Microsoft Access 2013 application program. Microsoft Access is a data processing application program that is well known to many people. For this reason, on this occasion the author designed an inventory management system using Microsoft Access 2013. The aim of this paper is to implement raw material inventory management using Microsoft Access. Based on the results of this research, it can make it easier to find information on raw material inventory data on NIKITOP. The information obtained in the raw material inventory is valid and accurate, the time required is faster and well controlled